(untitled) (Fourth World Journal, 2018)
For Andean people, economic, spiritual and social life, are inextricably tied to land and water. The Aymara of Chile are a small geographically isolated minority who are struggling to maintain their sustainable traditional systems of irrigation water distribution, agriculture, and pastoralism in one of the most arid regions of our world, the Atacama Desert. Together we explore the ethnoecological dimensions of the conflict between externally imposed unsustainable development and the Aymara Marka (Nation) sensitive cultural and natural resource base. The Aymara people are proactively engaged in protecting their sacred resources from further toxic mining, water pollution, diversion and appropriation, international highway development, landfills, hydroelectric and geothermal development, desecration of their natural and cultural properties, and introduction of GMOs into their organic sustainable agricultural and agropastoral systems in the most impoverished province of Chile, highland Parinacota